The impact of protection on observed productivity distributions - Igor Bagayev; Ronald B. Davies (University College Dublin, UCD School of Economics, 2017)
As is well established, one prediction of the heterogenous firms literature spearheaded by Melitz (2003) is that trade liberalization, by increasing import competition, drives less productive domestic firms from the market. This increases average productivity of the domestic economy via the "selection effect". In addition, it has the potential to affect the skewness of the observed productivity distribution, i.e. the gap between the productivity of the median firm and average productivity. We examine these predictions empirically using data on 28 sectors across 99 countries. On the whole, we find that higher protection levels lower average productivity and drive a larger wedge between mean and median productivity. This latter suggests that policy decisions based on mean outcomes may arrive at different conclusions than those based on median voters.
Keywords: F12; F13; 330; Non-tariff measures; Productivity distribution; heterogeneous firms